A novel 3D porous pseudographite/Si/Ni composite anode material fabricated by a facile method. Issue 21 (15th May 2020) - Su, Weiming; Wan, Ruchao; Liang, Yue; Zuo, Yinze; Tang, Yuefeng
Abstract : A novel 3D porous pseudographite/Si/Ni (PG/Si/Ni) composite was prepared by a facile low-temperature calcination method using saturable starch and NiCl2 ·6H2 O as precursors. Abstract : A novel 3D porous pseudographite/Si/Ni (PG/Si/Ni) composite was prepared by a facile low-temperature calcination method using saturable starch and NiCl2 ·6H2 O as precursors. The pseudographite matrix of PG/Si/Ni was obtained from the reaction between starch and NiCl2 ·6H2 O during the calcination process. Compared to the C/Si electrode, the PG/Si/Ni electrode delivers a high reversible specific capacity of 659.66 mA h g −1 at a current density of 1 A g −1 even after 2000 cycles. In addition, the PG/Si/Ni electrode shows superior rate performance and still maintains a high specific capacity of 1324.01 mA h g −1 when the cycle current density returns to 0.1 A g −1 . The porous pseudographite structure is able to improve Li + diffusion efficiency, reduce pulverization and lead to the formation of stable SEI layers during the cycling process. Therefore, these results suggest that the 3D porous pseudographite/Si/Ni composite is a promising novel anode material. Besides, the low-temperature synthesis method of the pseudographite matrix can be applied for further modification of carbon-based Si anode materials.